STUDENTS’ MOBILE TECHNOLOGY USAGE AND THEIR TOEFL LISTENING PROFICIENCY: A CORRELATIONAL STUDY - Nurwulandari, Wuri Alfi; Daud, Afrianto; Prawati, Atni (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2023)
This research aimed to find out the correlation between students’ mobile technology usage and TOEFL listening proficiency in the sixth semester of the English Study Program of FKIP Universitas Riau. The sample of this study was 36 students in the sixth semester of the English Study Program of FKIP Universitas Riau. The Cluster Random sampling technique was utilized to choose the sample for this research. This study used two data instruments, a mobile technology usage questionnaire and TOEFL listening proficiency gained by collecting students’ TOEFL listening scores. The instruments were distributed to the respondents online through Google Forms. The mobile technology usage questionnaire was an adaptation of a questionnaire by Grenier. The respondents submitted the TOEFL listening score after finishing the questionnaire. The students’ mobile technology usage was analyzed using a Likert scale in the form of positive questions. The students’ proficiency levels were categorized using ETS Performance Descriptors for TOEFL. The researcher used the Pearson Product Moment formula to determine the correlation coefficient value. The result of this study shows that most respondents’ listening proficiency is categorized at the elementary level with a range score of the listening section 31-46. Moreover, this study revealed a moderate correlation between students’ mobile technology usage and their TOEFL listening proficiency, with a 36% determinant score. In other words, mobile technology usage is not the main factor in determining students’ TOEFL listening proficiency.